Warming effects on spring phenology in New York City parks - Juwon Kong; Jeffrey A G Clark; Clara C Pregitzer; Fiona Jevon; Rasmus Houborg; Karen C Seto (Environmental Research Letters, 2025)
Global climate change and the urban heat island (UHI) interact to create unique urban microclimates. However, how these interactions affect trees in urban parks is poorly understood. Using multi-source satellite fusion, we observe that New York City parks are experiencing delays in the start of the growing season, especially in medium-sized parks. Notably, warming effects are more pronounced in park trees near the edges, where urban heat is stronger. This delay is explained by a physiological mechanism: warmer winters reduce chilling accumulation and increase the heat requirements for leaf development, disrupting the balance between chilling and heat needed for spring leaf-out. Medium-sized parks are especially vulnerable to urban heat due to their structural characteristics such as higher edge-to-area ratios and limited interior buffer zones, both of which amplify edge effects. These findings demonstrate that climate change, compounded by the UHI effect, is altering tree phenology in urban parks, with implications for urban ecosystem adaptation and management.